A Modified Model for Hotel Website Functionality Evaluation. Issue 9 (21st November 2016) - Leung, Daniel; Law, Rob; Lee, Hee "Andy"
ABSTRACT: Harnessing a mathematical computation approach to analyze data solicited from 354 website stakeholders (including 200 hotel customers, 83 hotel managers, and 71 hotel website designers), this study presents an up-to-date and robust evaluation model for assessing the functionality of hotel websites. The modified model was also empirically used to assess the functionality performance of the websites of all the hotels in Hong Kong. Results from the non-parametric Kruskal–Wallis and Mann–Whitney tests revealed a difference in performance, with higher star rating hotels performing better than those with a lower star rating. As one of the first attempts to incorporate the perceptions of multiple website stakeholders into hotel website evaluation, this study provides hoteliers with practical advice on website development.